Nucleação de vortices em nanoelementos elípticos - Oliveira, Felipe Fávaro de (2012)
The present work reports a theoretical study of the vortex nucleation in elliptical nanoelements of iron with the dimensions of the principal and secondary axes in the range of hundreds of nanometers. It will be divided into three steps: first of all, a general panorama and a justification for the interest of the study of nanosystems and their applications. Second, a explanation about the computational simulations applied for the calculations of the remanent states after the saturation in a external field which value is grater then the exchange field of the material for nanoelements coupled or not to a antiferromagnetic substrate. Systems with that range of axes dimensions and height in the range of a few dozens of nanometers have a natural tendency to nucleate closed magnetic ux, like vortex. Third, we will emphasize the nucleation of double vortex, the main types and the dimensions in which they occur (phase diagram) and the factors that may in uence in the nucleation and control of the remanent state. We shown that we can control specially the distance between the vortex cores changing the value of the interface field. Finally, we present a expectative of continuity of this work with objectives and applications